Democracy for idiots. Republicanism, self-alienation and permanent minorities - Álvarez Garcia, David (2016)
The main thesis can be summarized the following way: If freedom-status is the master good for republicans then, when democratic participation and mandatory citizenship undermine the self-respect of permanent minorities, self-alienation becomes a political status compatible with the republican ideal of freedom as non-domination. By self-alienation I understand the voluntary withdrawal of active democratic participation, the rejection of national membership as citizen, and the assumption of the status of permanent resident. The paper argues that permanent residency and national citizenship must be conceived as equivalent statuses in terms of non-domination and therefore, as compatible forms of democratic equality.